2013
DOI: 10.1097/qai.0b013e31828e6412
|View full text |Cite
|
Sign up to set email alerts
|

One-Arm, Open-Label, Prospective, Cohort Field Study to Assess the Safety and Efficacy of the PrePex Device for Scale-Up of Nonsurgical Circumcision When Performed by Nurses in Resource-Limited Settings for HIV Prevention

Abstract: The study demonstrated that circumcision performed by nurses using the PrePex device is safe, effective, and easy to train. The procedure was minimally invasive and did not require injected anesthesia, sutures, or sterile settings. PrePex has the potential to help facilitate rapid, safe, nonphysician male circumcision scale-up programs for HIV prevention, an imminent need in sub Saharan Africa where physicians are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
4
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 7 publications
6
50
4
1
Order By: Relevance
“…The observed rate of moderate/severe adverse events (1.4%) was similar to that reported in other PrePex studies [7], [9], [13], and comparable to rates with the Shang Ring device (1.0%) and dorsal slit surgery (0.8%) in this population [11] However, we observed 7 cases of participant self-removal of the PrePex device (2.0%), and 4 of these cases resulted in severe complications requiring immediate surgery. One Rwandan study observed two cases of self-removal in 518 PrePex procedures (0.4%) [7] but another Rwandan study of 144 PrePex recipients reported no cases [9] Unpleasant smell was reported by 71.8% of clients with 10.2% reporting that the odor was noticed by people in their vicinity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The observed rate of moderate/severe adverse events (1.4%) was similar to that reported in other PrePex studies [7], [9], [13], and comparable to rates with the Shang Ring device (1.0%) and dorsal slit surgery (0.8%) in this population [11] However, we observed 7 cases of participant self-removal of the PrePex device (2.0%), and 4 of these cases resulted in severe complications requiring immediate surgery. One Rwandan study observed two cases of self-removal in 518 PrePex procedures (0.4%) [7] but another Rwandan study of 144 PrePex recipients reported no cases [9] Unpleasant smell was reported by 71.8% of clients with 10.2% reporting that the odor was noticed by people in their vicinity.…”
Section: Discussionsupporting
confidence: 89%
“…One obstacle to MMC scale up in adolescents and adults is the time and provider skills required for conventional surgical procedures (forceps guided, dorsal slit and sleeve circumcision) all of which entail a surgical time of 15–45 minutes (depending on provider experience), aseptic conditions and skill in hemostasis and suturing for wound closure. Two devices, the Shang Ring [6] and the PrePex device [7][10] offer potential advantages in reduction of procedure time which could increase throughput of clients, a lower requirement for asepsis and the procedures can be performed by less skilled providers [7], [8], [10] which could facilitate task shifting and sharing. Both devices must be removed 5–9 days after placement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several technology developers are incorporating similar approaches or alternative methods for global health technology development. [55][56][57][58] Donors and global health policymakers need to understand in detail how these technologies are generated and to extract best practices/lessons learned to better foster development of sustainable global health technologies for resourcelimited settings.…”
Section: Discussionmentioning
confidence: 99%
“…Following clinical studies of PrePex in Rwanda [5,6,7] and other unpublished reports, WHO pre-qualified PrePex for use in national VMMC programs [8]. Pilot implementation studies of the device were then conducted, including one conducted in routine service delivery by our team in western Kenya [9].…”
Section: Introductionmentioning
confidence: 99%